Boron Supply Enhances Aluminum Tolerance in Root Border Cells of Pea (Pisum sativum) by Interacting with Cell Wall Pectins - Li, Xue Wen; Liu, Jia You; Fang, Jing; Tao, Lin; Shen, Ren Fang; Li, Ya Lin; Xiao, Hong Dong; Feng, Ying Ming; Wen, Hai Xiang; Guan, Jia Hua; Wu, Li Shu; He, Yong Ming; et al. (Frontiers in Plant Science, 2017)
Aluminum (Al) toxicity is the primary factor limiting crop growth in acidic soils. Boron (B) alleviates Al toxicity in plants, which is mainly considered to be due to the formation of Rhamnogalacturonan II-B (RGII-B) complexes, which helps to stabilize the cytoskeleton. It is unclear yet whether this is due to the increasing of net negative charges and/or further mechanisms. Kinetics of Al accumulation and adsorption were investigated using entire cells, cell wall and pectin of root border cells (RBCs) of pea (Pisum sativum), to reveal the mechanism of B in interacting with alkali-soluble and chelator-soluble pectin for an increased Al tolerance in RBCs. The results show that B could rescue RBCs from Al-induced cell death by accumulating more Al in the cell wall, predominately in alkali-soluble pectin. Boron also promotes Al3+ adsorption and inhibits Al3+ desorption from alkali-soluble pectin. Thus, more Al3+ is immobilized within the alkali-soluble pectin fraction and less in the chelator-soluble pectin, rendering Al3+ less mobile. Boron induces an increase of RG-II (KDO,2-keto-3-deoxyoctonic acid) content for forming more borate-RGII complexes, and the decrease of pectin methyl-esterification (DM), thus creates more negative charges to immobilize Al3+ in cell wall pectin. The study provides evidence that abundant B supply enhances the immobilization of Al in alkali-soluble pectin, thus most likely reducing the entry of Al3+ into the symplast from the surroundings.